Injuries during transition periods across the year in pre-professional and professional ballet and contemporary dancers: A systematic review and meta-analysis. (July 2020) - Fuller, M.; Moyle, G.M.; Hunt, A.P.; Minett, G.M.
Abstract: Objective: To consider the association of injuries with transition periods in the dance year, i.e., when dancers return at the start of the year, and when they transition from rehearsal to performance periods. Methods: Six electronic databases were searched to November 2019. All English language peer-reviewed studies, of any study design investigating ballet and contemporary pre-professional and professional dance populations were included. Only those studies reporting on the timing of injury were included. Results: Fifteen cohort and two case-series studies were included. A meta-analysis of seven studies revealed the rate of injuries to be significantly higher for the second and third months (1.52; 95% confidence interval [CI]:1.11–2.08; 1.26; 95%CI:1.07–1.48 respectively) after the return to dance. Two further studies report more injuries up to Week 13 of the year. One study showed an increase in injured dancers at three and four weeks after transition from rehearsals to a performance season. Four studies show an increase in injuries at performance times. Conclusions: Meta-analyses of seven studies shows the second and third months after returning to dance have a significantly higher rate of injuries. More research is needed to quantify training loads in dance. Practitioners should be cognisant of the higher injury rates during periods of transition and consider modifying load, as it is a potential contributing factor. Highlights: Seven studies were pooled for meta-analysis of injury rate ratio per month. Second and third months when dancers return to start the year have higher injuries. Five studies show injuries occur during transition from rehearsal to performance. Practitioners should consider modifying loads at identified times of the year.